1969
DOI: 10.1017/s0003356100026751
|View full text |Cite
|
Sign up to set email alerts
|

A study of factors affecting the voluntary intake of food by cattle

Abstract: Six diets providing ratios of concentrate to hay of 100 : 0, 95 : 5, 90 : 10, 80 : 20, 70 : 30 and 60 : 40 were given ad libitum to 24 British Friesian steers. The hay (in the long form) was offered separately from the concentrates. From 91 to 136 kg live weight, as the proportion of hay in the diet increased, daily dry-matter intake decreased. Over the weight range, 136 to 363 kg live weight, the addition of small amounts of hay to the concentrate diet caused an increase in intake. At 42 weeks of age a digest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

1970
1970
2008
2008

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 16 publications
1
5
1
Order By: Relevance
“…digestibility of feeds in the present study and the relationship between the two was low, even though seven out of eight forages had D.M. digestibilities lower than 66-7% up to which Conrad, Pratt & Hibbs (1964) suggested this relationship operated in cattle and below 70% DMD at which McCullough (1969) suggested that sheep regulated their energy intake. These results on buffaloes are, however, in agreement with those of Greenhalgh & Runcie (1962), Elliot & Topps (1963), Van Soest (1965 and Murdoch (1967) on cattle and sheep who observed either no or low relationships between intake of feeds and their digestibility.…”
Section: Discussioncontrasting
confidence: 57%
“…digestibility of feeds in the present study and the relationship between the two was low, even though seven out of eight forages had D.M. digestibilities lower than 66-7% up to which Conrad, Pratt & Hibbs (1964) suggested this relationship operated in cattle and below 70% DMD at which McCullough (1969) suggested that sheep regulated their energy intake. These results on buffaloes are, however, in agreement with those of Greenhalgh & Runcie (1962), Elliot & Topps (1963), Van Soest (1965 and Murdoch (1967) on cattle and sheep who observed either no or low relationships between intake of feeds and their digestibility.…”
Section: Discussioncontrasting
confidence: 57%
“…In another study, Slabbert and colleagues (1992b) fed cattle with 30%, 55%, and 80% concentrate and found that ADG increased as concentrate level increased. One reason given for the observed increase in ADG among cattle receiving an increasing level of concentrate is that these cattle had an increased level of propionate and a decreased level of acetate in their rumen (Slabbert et al, 1992a, McCullough, 1969 Since this study examines the cultural energy expended and deposited during feedlot feeding in order to avoid bias, energy deposited in cattle before feeding in feedlot had to be calculated. This was explaned the in Materials and Methods section and was referred to as weaning carcass energy.…”
Section: Resultsmentioning
confidence: 99%
“…A . MCCULLOTJGH various concentrate supplemented diets used by McCullough (1969) with stage of growth even though Blaxter, Clapperton & Wainman (1966) showed that there was no systematic trend with age of animal in the apparent digestibility when feeding at different levels of intake. Furthermore, Blaxter & Wilson (1963) in a study of sheep given a series of roughage diets with the addition of increasing proportions of concentrate showed that the quality of roughage affects the total drymatter intake.…”
Section: Introductionmentioning
confidence: 99%